2017
DOI: 10.1016/j.biopha.2017.05.135
|View full text |Cite
|
Sign up to set email alerts
|

Qa-2 expression levels is related with tumor-infiltrating lymphocytes profile during solid Ehrlich tumor development

Abstract: The Qa-2 has been described as Human Leucocyte Antigen G (HLA-G) murine homolog. This homology is well accepted to gene and protein structure, in different pathology process and embryos implantation. However, in some neoplasm, this homology is questioned, where Qa-2 has been proposed as an immunogenic molecule, associated to tumor rejection. In this way, the aim of this study was to describe the pattern of Qa-2 expression and its relationship with the profile of tumor-infiltrating lymphocytes in solid Ehrlich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…The streptavidin-peroxidase (SP) method was used for immunohistochemical staining using the Kit Ultra vision large volume anti-polyvalent detection system, HRP-Lab Vision, DAKO, as described [63]. The antibody used was Anti-caspase-3 (dilution 1:600—Cell Signaling Technology, Danvers, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The streptavidin-peroxidase (SP) method was used for immunohistochemical staining using the Kit Ultra vision large volume anti-polyvalent detection system, HRP-Lab Vision, DAKO, as described [63]. The antibody used was Anti-caspase-3 (dilution 1:600—Cell Signaling Technology, Danvers, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Peritumor inflammatory infiltrates in SEC are composed of mononuclear and polymorphonuclear leukocytes, with moderate intensity between days 2 and 7 post-inoculation. Da Silva et al also showed a positive correlation between the intensity of inflammatory infiltrate and animal weight and tumor size ( 41 ). The main lymphocytes are CD3 + , CD4 + , CD8 + , and Foxp3.…”
Section: Immune and Systemic Alterations Caused By Ehrlich Tumorsmentioning
confidence: 97%
“…The main lymphocytes are CD3 + , CD4 + , CD8 + , and Foxp3. Increases in CD3 + and Foxp3 and decreases in CD4 + and CD8 + were linked with tumor development ( 41 ). Additionally, SEC cells that were inoculated in the intraplantar area in mice were characterized by local neutrophilic infiltration with an extensive necrotic area, which may be responsible for mechanical allodynia, thermal hyperalgesia, and paw edema ( 42 ).…”
Section: Immune and Systemic Alterations Caused By Ehrlich Tumorsmentioning
confidence: 99%
“…In the case of tumours controlled by cytotoxic T cells, studies into Qa-2 expression are not clear, although current research tends to report anti-tumorigenic properties of Qa-2. In the case of 4T1 breast cancer (da Silva et al, 2017a), B16 melanoma (Chiang and Stroynowski, 2004) and Ehrlich tumours (da Silva et al, 2017b), all of which are controlled by cytotoxic T lymphocytes (CTLs), Qa-2 expression is positively correlated with tumour clearance. However, there are also two conflicting studies by the same group examining Qa-2 in NK-cell sensitive tumours.…”
Section: H2-q Familymentioning
confidence: 99%